ANALYSIS OF THE STRUCTURE OF EXPORT AND IMPORT OF GOODS BETWEEN THE REPUBLIC OF POLAND AND THE RUSSIAN FEDERATION - V. A. Kardanov; V. N. Kulik; T. A. Petrova; V. V. Vulshonok (Вестник университета)
The issues related to the analysis of export and import of goods between two neighboring states: the Republic of Poland and the Russian Federation have been examined. Relations between the EU countries and Russia to date have been in a significant crisis. Cooperation in the economic field is reduced in the context of mutual sanctions. According to the authors, for the Russian Federation in the near future the main task should be set – economic rapprochement with the countries of the European Union and further negotiations on easing mutual sanctions, since these and other reasons significantly complicate the countertrade in goods and services and impede European integration. It is obvious, that European companies are also interested in normalizing commercial and economic relations. The limitations of non-tariff regulation in foreign trade have been considered also in the paper. It has been concluded on the need to gradually mitigate restrictive measures. And efforts in this direction should be made by both the Russian Federation and the member States of the European Union, including the Republic of Poland.